Asthma and Academic Performance Among Children and Youth in North America: A Systematic Review. (30th January 2020) - Schneider, Tali
ABSTRACT: BACKGROUND: The increasing prevalence of asthma among adolescents and the limited studies exploring the educational outcomes for youth coping with asthma makes the inquiry in this field of special interest. This paper reviews the literature on empirical studies exploring the relationship between asthma and academic performance among adolescents. METHODS: Five databases ( CINAHL, PubMed, ERIC EBSCO, Web of Science, and PsycINFO) were searched for peer‐reviewed empirical studies exploring the link between asthma and academic performance utilized. Studies were reviewed, logged, and assessed studies for their research design, methods, and findings. Data synthesis incorporated strengths, limitations, and recommendations for future research and practice. RESULTS: Twenty studies met the inclusion criteria. Of these, 13 employed a survey design and 7 evaluated school‐based interventions implementing an experimental design. Whereas researchers applied quantitative methods in all the studies, qualitative and mixed‐method designs were infrequently used. Studies showed a link between school absenteeism and asthma; other academic indicators (eg, graduation and test‐scores) showed inconsistent correlation. CONCLUSIONS: Future research should deploy more variable research designs and methods to improve understanding of the factors contributing to the relationship between adolescent asthma and academic performance. Additional topic‐specific inquiry is needed to inform school practices and policies.